DYNAMIC OF INTESTINAL PERMEABILITY IN CANCER PATIENTS DURING PERIOPERATIVE PERIOD - A. Yu. Karpenko; D. S. Tsvetkov; M. V. Kiselevsky (Сибирский онкологический журнал, 2016)
Intestinal mucosa is a barrier, preventing bacteria and it’s derivate from penetrating to organism, where it triggers inflammation. In this study the dynamic of intestinal permeability in cancer and cardio surgery patients during perioperative period is evaluated using dual sugar test (lactulose-mannitol). Lactulose and mannitol excretion ratio is increased in group of cancer patients with postoperative complications before and after surgery. This indicates an increased intestinal permeability in these patients. Probably increased permeability cause bacterial lipopolysaccharide translocation into blood, where it induces effectors of innate immunity, leading to system inflammation reaction due to already activated immunity. According to this, evaluation of intestinal permeability can be considered as a prognostic factor of unfavorable early postoperative period in cancer patients.